Production, Viscosity, Microbiological Quality and Sensory Properties of Complementary Food Blends of Improved Rice Cultivars, Soybean and Sorghum Malt - Badau, Mamudu H.; Bristone, Charles; Igwebuike, Joseph U.; Danbaba, Nahemiah (Pakistan Journal of Nutrition, 2016)
Production methods, viscosity, microbiological quality and organoleptic properties of complementary food formulations from mixtures of improved rice cultivars (broken fractions of FARO 44, FARO 52, NERICA L – 34, NERICA L – 19) and local rice (yar Mubi), sorghum malt and soybean (Glycine max - yar Jalingo) flour blends used for infant formulas were characterized. A 5x2x2 factorial in a completely randomized design comprising 5 rice cultivars, sorghum malt (0.5%) and soybean flour (0, 30%) were used to produce 20 formulations that were evaluated for viscosity, microbiological and sensory properties. Appropriate blends with suitable viscosity for infant feeding were considered as criteria for subsequent studies (70% rice, 30% soybeans with malt). Viscosity of 10% and 20% gruel of rice cultivars, sorghum cultivar, sorghum malt and soybean flours ranged from 1035.33 to 1957.73 cp and 1816.53 to 3024.57 cp, respectively. Gruel prepared with malt had reduced viscosity compared to that where malt was added later. Microbial analysis revealed a total plate count of 2.0 x 106 to 7.2 x 106 CFU/g, an aerobic plate count of 1.76 x 106 to 4.1 x 106 CFU/g and a yeast-mould count of 0.1 x 106 to 0.2 x 106 CFU/g. The bacterial species isolated included Staphylococcus saprophyticus, Staphylococcus epidermidis, Bacillus megaterium, Bacillus thuringiensis and Micrococcus species. Fungi species isolated included Rhodotorula Sp., Aspergillus Sp., Mucor Sp. and Alternaria Sp. Sensory attribute studies of 20 weaning mothers showed no significant (P>0.05) variation compared to conventionally complementary food. Complementary food formulations with a broken fraction of rice basis thus mimicked high-grade conventional complementary rice food (Friso-Gold) in terms of sensory attributes.